Epigenetic regulation in fibrosis progress. (November 2021) - Xue, Taixiong; Qiu, Xingyu; Liu, Hongyao; Gan, Cailing; Tan, Zui; Xie, Yuting; Wang, Yuxi; Ye, Tinghong
Abstract: Fibrosis, a common process of chronic inflammatory diseases, is defined as a repair response disorder when organs undergo continuous damage, ultimately leading to scar formation and functional failure. Around the world, fibrotic diseases cause high mortality, unfortunately, with limited treatment means in clinical practice. With the development and application of deep sequencing technology, comprehensively exploring the epigenetic mechanism in fibrosis has been allowed. Extensive remodeling of epigenetics controlling various cells phenotype and molecular mechanisms involved in fibrogenesis was subsequently verified. In this review, we summarize the regulatory mechanisms of DNA methylation, histone modification, noncoding RNAs (ncRNAs) and N6-methyladenosine (m6A) modification in organ fibrosis, focusing on heart, liver, lung and kidney. Additionally, we emphasize the diversity of epigenetics in the cellular and molecular mechanisms related to fibrosis. Finally, the potential and prospect of targeted therapy for fibrosis based on epigenetic is discussed. Graphical Abstract: ga1 Highlights: The process of organ fibrosis involves extensive epigenetic remodeling. Epigenetic mechanism in fibrosis mostly depends on the regulation in the expression of fibrotic genes. Epigenetic therapy presents a potential strategy for fibrosis treatment.